49. THE BENEFITS OF BREASTFEEDING ON BREAST CANCER RISK IN VIETNAM (Vietnam Journal of Community Medicine, 2024)
Objective: This study aims to determine the association between breastfeeding and breast cancer risk in Vietnamese women.Subjects and Methods: A case - control study involving 370 breast cancer patients, and 370 controls was conducted at Ho Chi Minh city Oncology Hospital from September 2023 to July 2024. A conditional logistic regression model was used to estimate the odds ratio (OR) and 95% confidence interval (CI) to evaluate the association between breastfeeding and breast cancer risk.Results: Women who breastfed had a reduced risk of breast cancer compared to those who did not (OR = 0.59; 95%CI: 0.37-0.95; p = 0.03). Women who breastfed for 12 months or more had a lower risk of the disease compared to those who breastfed for less than 12 months (OR = 0.51; 95%CI: 0.33-0.79; p = 0.002). Women who breastfed two or more children had a reduced risk of breast cancer compared to those who breastfed fewer than two children (OR = 0.47; 95%CI: 0.31-0.71; p < 0.01). The average breastfeeding duration per child of more than 6 months was associated with a lower breast cancer risk compared to an average duration of less than 3 months (OR = 0.47; 95%CI: 0.29-0.75; p < 0.01).Conclusions: These results highlight the crucial role of extended breastfeeding in the prevention of breast cancer.
Keywords: Breastfeeding; breast cancer; case - control study; risk factors